2018
DOI: 10.1063/1.5042028
|View full text |Cite
|
Sign up to set email alerts
|

Impact of operating temperature on the electrical and magnetic properties of the bottom-pinned perpendicular magnetic tunnel junctions

Abstract: Analogous device parameters in both the parallel (P) and anti-parallel (AP) states ensure a symmetric spin-transfer-torque magnetic random-access memory operation scheme. In this study, however, we observe an increasing asymmetry in the performance metrics with operating temperature of the bottom-pinned perpendicular magnetic tunnel junction (p-MTJ) devices. A temperature-dependent increase in the contribution of the stray field is observed in the tunneling magnetoresistance loop analysis. The switching curren… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 21 publications
0
6
0
Order By: Relevance
“…The magnetization (m PL ) of the PL is strongly pinned to a certain direction by an inner synthetic anti-ferromagnet (iSAF) [76]. With the fixed magnetization in PL as a reference, the magnetization in FL is either parallel (P state) or anti-parallel (AP state) to that of PL, as illustrated with the left and right device schematics, respectively, in Figure 3 Note that the real-world MTJ stack designs are much more complicated; the MTJ stack may consist of more than 10 thin films to enhance the device performance, as can be found in [76,[78][79][80]. For example, it is found that adding an MgO capping layer, the white line above the FL in Figure 3.1b is very effective in enhancing the thermal stability [78].…”
Section: ) Pinned Layer (Pl)mentioning
confidence: 99%
See 2 more Smart Citations
“…The magnetization (m PL ) of the PL is strongly pinned to a certain direction by an inner synthetic anti-ferromagnet (iSAF) [76]. With the fixed magnetization in PL as a reference, the magnetization in FL is either parallel (P state) or anti-parallel (AP state) to that of PL, as illustrated with the left and right device schematics, respectively, in Figure 3 Note that the real-world MTJ stack designs are much more complicated; the MTJ stack may consist of more than 10 thin films to enhance the device performance, as can be found in [76,[78][79][80]. For example, it is found that adding an MgO capping layer, the white line above the FL in Figure 3.1b is very effective in enhancing the thermal stability [78].…”
Section: ) Pinned Layer (Pl)mentioning
confidence: 99%
“…For example, it is found that adding an MgO capping layer, the white line above the FL in Figure 3.1b is very effective in enhancing the thermal stability [78]. Furthermore, the PL consists of a reference layer (RL), composed of Co/Ru/CoFeB, and a hard layer (HL), composed of [Co/Pt] x ; The RL and HL are anti-ferromagnetically coupled [80].…”
Section: ) Pinned Layer (Pl)mentioning
confidence: 99%
See 1 more Smart Citation
“…Since H offset is essentially equivalent to the extra external field applied to cancel out H s intra , the relation of these two parameters is H s intra = −H offset . Given the fact that the resistance-area product (RA) does not change with the device size, the electrical Critical Diameter (eCD) of each device can be derived by [18]:…”
Section: Intra-cell Magnetic Coupling Characterizationmentioning
confidence: 99%
“…Since H offset is essentially equivalent to the extra external field applied to cancel out H s intra , the relation of these two parameters is H s intra = −H offset . Given the fact that the resistance-area product (RA) does not change with the device size, the electrical Critical Diameter (eCD) of each device can be derived by [18]: eCD = 4 π • RA RP , where RA=4.5 Ω • µm 2 (measured at blanket stage) for this wafer, and R P can be extracted from the R-H loop (i.e., the lower horizontal line in Fig. 2a).…”
Section: Intra-cell Magnetic Coupling Characterizationmentioning
confidence: 99%